Use of bone grafts in oral rehabilitation with implants (Research, Society and Development, 2024)
Introduction Bone loss occurs after tooth extraction, physiologically due to aging, after accidents, periodontitis or even due to the use of mobile prostheses supported on the edentulous ridge. This phenomenon contributes in some way to limiting rehabilitation with osseointegrated implants. Therefore, it is necessary to perform bone grafting techniques. Objective: to analyze the use of bone grafts in oral rehabilitation with implants. Methodology: This research is an integrative literary review. The scientific basis was carried out in the following databases: Virtual Health Library, Scientific Electronic Library Online and PubMed, using search terms such as dental implants, bone grafts, bone resorption, osseointegrated dental implant, covering the period from 2007 to 2023. Results: According to the eligibility criteria, 20 articles were found, after screening the literature, 14 articles were included and had data tabulated. Conclusion: Its effectiveness is concluded through studies in rehabilitation with dental implants and the correct indication of the type of graft to be used is an essential factor in the bone regeneration process for the success of the procedure.